Minipuberty: Looking Back to Understand Moving Forward - Lucaccioni, Laura; Trevisani, Viola; Boncompagni, Alessandra; Marrozzini, Lucia; Berardi, Alberto; Iughetti, Lorenzo (Frontiers in Pediatrics, 2021)
Hypothalamic-pituitary-gonadal (HPG) axis activation occurs three times in life: the first is during the fetal life, and has a crucial role in sex determination, the second time is during the first postnatal months of life and the third is with the onset of puberty. These windows of activation recall the three windows of the “Developmental Origin of Health Disease” (DOHaD) paradigm and may play a substantial role in several aspects of human development such as growth, behavior, and neurodevelopment. From the second trimester of pregnancy there is a peak in gonadotropin levels, followed by a decrease towards term and complete suppression at birth. This is due to the negative feedback of placental estrogens. Studies have shown that in this prenatal HPG axis activation, gonadotropin levels display a sex-related pattern which plays a crucial role in sex differentiation of internal and external genitalia. Soon after birth, there is a new increase in LH, FSH and sex hormone concentrations, both in males and females, due to HPG re-activation. This postnatal activation is known as “minipuberty”. The HPG axis activity in infancy demonstrates a pulsatile pattern with hormone levels similar to those of true puberty. We review the studies on the changes of these hormones in infancy and their influence on several aspects of future development, from linear growth, to fertility and neurobehavior.